PHYTOCHEMICAL SCREENING AND ANTIDEPRESSANT ACTIVITY OF LEAVES EXTRACT OF DESMODIUM GANGETICUM - Malviya, Mr. Bablu; Patel, Mr. Narendra; Tyagi, C.K.; Budholiya, Prabhakar (Journal of Biomedical and Pharmaceutical Research, 2021)
According to Biological Conservation Letter, more than 7,000 species of plants found in various ecosystems are said to be medicinal in the country. So, India is one of the world’s richest sources of medicinal and aromatic plants. Desmodium gangeticum is an important medicinal plant. It is commonly used in ayurvedic formulations for the treatment of various disorders. Phytochemical evaluations, pharmacogonostic evaluation, organoleptic characters, TLC profile was carried out to set them as diagnostic indices for the identification/validation of the raw material and standardization of the formulations. Preliminary phytochemical analysis showed the presence of active constituents which is necessary for the pharmacological activity. Organoleptic properties, phyto-chemical studies, powder analysis, showed the presence of adulteration in the powder. Majority of the antidepressant drugs improve depressive symptoms, but they exert multiple undesirable side effects. The search for more productive and well tolerated drugs is in progress. Phytochemical analysis of Desmodium gangeticum revealed the presence of alkaloids, phenols, flavonoids, Saponins, Steroids. Desmodium gangeticum is a well known medicinal plant as anti-inflammatory, antimicrobial and nephroprotective etc. It is a very good drug for urinogenital problems, hepatic problems, oxidative stress etc. The present study was depict to evaluate the antidepressant activity of hydroalcoholic extract of Desmodium gangeticum in mice. It was evaluated using the Tail Suspension Test (TST) and Forced Swimming Test (FST) in mice. Desmodium gangeticum (200 and 400 mg/kg) was administered orally in separate groups of Swiss albino mice weighing 20-25 for 14 days in TST and FST tests.. The Leaves extract of Desmodium gangeticum showed a dose dependant reduction in duration of immobility in mice. The dose of 400 mg/kg of Leaves extract of Desmodium gangeticum significantly reduced the immobility time of mice in both FST and TST. The effectual of extract was found to be similar to fluoxetine (20 mg mg/kg, po). It was found to be toxicologically safe with no deaths of mice when administered orally at the dose of 2000 mg/kg. From the current study, it can be concluded that the Leaves extract of Desmodium gangeticum possess dominant antidepressant activity as reveal by the TST and FST tests and is toxicologically safe.